Pemikiran Modern Dalam Konteks Islam Global - N, Nurfadillah; Usman, Abdurrahim Supardi; Zain, Muhammad; Fahira, Jihan; Rama, Bahaking (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Modern thought in Islam is a dynamic response to changes in the era marked by advances in science, globalization, and modernization. In a global context, Islam not only faces internal challenges, such as conservatism and intellectual stagnation, but also external challenges in the form of Western thought currents that often conflict with traditional Islamic values. Therefore, there is a need to understand the characteristics of modern thought in Islam and how it develops as part of the global discourse. In this study, the author reveals modern Islamic thought by collecting data from a literature review. The results of this study indicate that modern Islamic thought and globalization are themes that reflect the complexity of the interaction between religious values and the dynamics of the modern world. Although Muslim communities face various challenges in facing globalization—including cultural integration, economic equality, and minority rights—there are also significant opportunities for positive contributions and adaptation. By utilizing technology, contributing to the global economy, and expressing Islamic culture on the international stage, Islam can play an important role in shaping the future of a more just and connected world. Understanding and facing these challenges wisely, while taking advantage of the opportunities that exist, will enable Muslim communities to play an active and positive role in the ever-evolving global context.